THE COMPACT WITH THE CHARTER AND LAWS OF THE COLONY OF NEW PLYMOUTH 102 (William Brigham ed., 1836) (enacted 1675) (Year-Round) - (:unkn) unknown (General Publisher, 1675)
Required everyone to bring arms to Sunday church services, furnishing six charges of powder and shot. The penalty is two shillings for violations.
Keywords: REQUIRED POSSESSION